Optical storage properties in cast films of an azopolymer - Neves, Ubaldo Martins Das; Santos Junior, David Sotero Dos; Giacometti, José Alberto [UNESP]; Zílio, Sergio Carlos; Misoguti, Lino; Balogh, Débora Terezia; Oliveira Junior, Osvaldo Novais De; Mendonça, Cleber Renato (ABM, ABC, ABPol, 2003)
In this paper we discuss the properties of optically induced birefringence in DR19-MDI cast films that may be used in optical storage applications. The selection of DR19-MDI cast films was based on a comparative study of optical storage properties of Langmuir-Blodgett (LB) films from various azopolymers. DR19-MDI possesses a high residual fraction of optical birefringence and good environmental stability, which was corroborated by the data from optical storage experiments. DR19-MDI cast films maintain a reasonable level of birefringence after the initial decay due to chromophore relaxation, thus making them promising candidates for optical storage devices.
Keywords: azopolymers; birefringence; optical storage